DISTRIBUSI PENCEMARAN DI PERAIRAN MUARA SUNGAI RIAU, KOTA TANJUNGPINANG, KEPULAUAN RIAU - Aras Mulyadi; Sofyan Husein Siregar; Irvina Nurachmi (Program Pascasarjana Universitas Riau, 2011)
Tanjungpinang city has developed so rapidly. This development is feared will give badimpact to the quality of the waters of Riau River Estuary because it deals directly with thevarious activities which taking place in the Tanjungpinang city. This research was carriedout by the method of survey in August 2011; aims to determine the potential and thedistribution of environmental pollution in the waters of Riau River Estuary. Identification ofpollution potential is sourced from marine (marine based) such as fisheries, ship traffic andmooring boats; and from land (land based) mainly urban waste, residential, hotel andrestaurant, tourism, agriculture, industry and mining. The majority of water quality ismeasured has exceeded the quality standard limit of waters Kepmen LH RI. 51/2004 inAppendix III (for marine biota life).